Pengembangan Etika dan Nilai Olympis dalam Mengajar Pendidikan Jasmani dan Olahraga - Rachmat Kasmad (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: This paper discussed the role of sport in modern development that need to be addressed critically. Modern life makes kids, teen, even parents only move within a narrow room. They exercise less, resulting in excess weight, and other diseases. They need the exercise. Exercise can actually display the lesson of life for one’s ethics. However, implementation of the sport requires a knowledge or education, which will direct a person to exercise properly and correctly. The presence of Olympics (competition) makes a lot of people who exercise justifies any means. Therefore, educator, teacher, or coach must be wise in putting the competition in learning of physical education and sports. Keyword: Sport, Physical Education, Ethics, Olympism, and Teaching.